Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Fiqih di Kelas V MI Sabilun Najah Penataran 02 - Efin Setiabudi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Looking at some indications, such as student learning outcomes, especially in Fiqh subjects, which have not been satisfactory, many students are passive and they are still afraid to ask the teacher if there is something they do not understand, also the courage of students to speak is still lacking, because the teacher does not familiarize students with trying. looking for answers and asking questions. Related to the indications above, the authors argue that the model plays an important role in the teaching and learning process because the success or failure of a learning is strongly influenced by an effective model in an institution. This research uses the Classroom Action Research method. Classroom action research is part of action research, and research at this level is part of qualitative research. In this study, the researcher wanted to know how to apply the Problem Based Learning model and how the learning outcomes from the application of the Problem Based Learning model in Fiqh Class V MI Sabilun Najah Penataran 02 learning. can improve student learning outcomes of class V MI Sabilun Najah Upgrading 02 the subject of understanding the provisions of Zakat Fitrah. This can be seen in the post test cycle I students who scored <75 as many as 6 students (24%) and students who scored >75 as many as 19 students (76%) with a class average of 84.4 While the post test scores in the second cycle students who scored <75 were 0 students (0%) and students who scored >75 were 25 students with a class average of 93.2. In the second cycle, student learning outcomes increased with a 100% completeness percentage. This is based on the minimum completeness criteria (KKM) that have been met, which is 75.